COFFEE RADIO: MARKETING STRATEGI DAN SWOT ANALYSIS - , AMIN SRI RAHAYU, Nur Endah Nugraheni, S.S.,MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This graduating paper aims at giving brief information about Coffee Radio. Then, it is to determine the marketing strategy used by Coffee Radio based on marketing mix using 7p. Additionally, this paper describes customer opinions about the place, product, price, promotion, people, process and physical evidence also general comment of Coffee Radio. The methods of collecting data are library research and field study. In the library research, the present writer studies several books, magazines, and materials from the internet which are related to the objects of the research. For field study, the present writer interviews the owner of Coffee Radio. In addition, the present writer also collects the data from questionnaire about 7p in Coffee Radio. From the questionnaire results, the present writer knows the opinion of the visitor such as place, product, price, promotion, people, process and physical evidence of and general comment Coffee Radio then analyze using SWOT. In conclusion, Coffee Radio is one cafe that creates cafe with a new atmosphere and homey concept for young people in Klaten and become one of famous place to hang out. Based on the questionnaire, the criteria of the place, product, price, promotion, people, physical evidence and process offered were excellent but the facilities provided still need mostly to be improved.